Influence of Social Media on Children's Dietary Habits : Pengaruh Media Sosial terhadap Kebiasaan Pola Makan Anak - Ashour , Qasim Kadhim (Indonesian Journal on Health Science and Medicine, 2025)
Introduction: Dietary habits refer to the consistent choices made by individuals or groups concerning their food consumption. It has a crucial influence in human health and reflects individual eating choices, which are often associated with culture, education, social background, and health status. Dietary habits may be influenced and altered by life stages and lifestyle factors, including physical activity and social interaction. Nutritional consumption significantly influences human health and well-being, particularly during childhood and adolescence, and directly impacts children's health due to their physical, mental, and cognitive development. Ap-proaches: Data has been gathered from 100 children to evaluate the impact of social media on their dietary practices. The question-naire was administered to professionals to establish its validity and subsequently its reliability. The total number of items in the questionnaire was 19. To evaluate children's behavior on social media about eating practices. The data was gathered by a simple random sampling process and analyzed using both descriptive and inferential statistical techniques. Outcomes The results indicated that among 100 children, the mean age of participation was 15.66 years. The current study demonstrated a moderate impact of so-cial media on children's food habits. The study demonstrated a substantial statistical link between children's age and hours spent on social media, as well as the impact of social media on children's food habits (p < 0.05). The results indicated no statistically signifi-cant differences (p > 0.05) between social media usage and other demographic variables. Concludes The findings indicated that so-cial media exerted a moderate influence on children's food habits. The study concluded that a substantial statistical link exists be-tween children's age, hours of social media usage, and the impact of social media on children's food habits. The results indicated no significant statistical differences between social media usage and other demographic variables. Highlights: Introduction: Dietary habits affect health, influenced by culture, education, and life stages. Approach: Data from 100 children analyzed the impact of social media on food. Outcomes: Social media moderately influences children's food habits; age and usage linked. Keywords: social media, Children, Dietary Habits, Directorate General of Education